Legal Strategies in Empowering Msmes Through Assistance to Support The Local Economic Ecosystem in Banyuanyar Village - Itok Dwi Kurniawan; Dara Pustika Sukma; Ismawati Septiningsih; Bambang Santoso; Muhammad Rustamaji; Jose Gama Santos (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a vital pillar of the national economy due to their contribution to job creation and local economic resilience. However, in rural areas such as Banyuanyar Village, MSMEs still face serious challenges, particularly in terms of business legality. Limited understanding of the importance of business licensing, restricted access to information, and financial constraints remain the main obstacles for MSME actors to obtain proper legal status. In response to these challenges, an assistance program was implemented with the aim of optimizing the legality of MSME products through three main approaches: education, technical assistance, and financial facilitation. The activities were carried out using interactive lectures, Focus Group Discussions (FGD), and participatory approaches (Built-in Participatory). The results of the FGD revealed that Banyuanyar Village already has an economic potential based on the concept of "One Village One Product." However, most MSME products still lack legal protection such as Intellectual Property Rights (IPR). Following the assistance, there was an increase in community awareness regarding the registration of IPR for their products, along with concrete support from the Village Government in facilitating the process. In conclusion, participatory legal assistance has proven to be effective in strengthening a legal, inclusive, and sustainable MSME ecosystem at the village level. This aligns with Sustainable Development Goals (SDGs) 8: Decent Work and Economic Growth.